Expression profiling of heat shock genes in a scuttle fly Megaselia scalaris (Diptera, Phoridae). Issue 10 (18th October 2015) - Malewski, Tadeusz; Bogdanowicz, Wiesław; Durska, Ewa; Łoś, Marta; Kamiński, Marcin; Kowalewska, Katarzyna
ABSTRACT: The Phoridae are a family of small, hump‐backed flies, dominating in post‐fire areas. Some of these flies are probably able to survive a fire as an egg, larva, or pupa, and may be adapted to the fire‐altered environment at the genomic level. In this study, we describe the influence of short‐term temperature treatment on the expression of seven heat shock protein genes in the third‐instar larvae and imagoes of a scuttle fly Megaselia scalaris —one of the cosmopolitan and polyphagous phorids. In terms of the response to temperature treatment, these genes tested against tubulin as a reference split into three classes. The first class consists of hsp22 (larvae), hsp23 (larvae), and hsp26 (both larvae and imagoes), and is upregulated at the lowest temperature (33°C). The second class consists of hsp22 (imagoes), hsp23 (imagoes), hsp40 (larvae and imagoes), and hsp70 (larvae and imagoes), and is upregulated or induced at 37°C. Expression of genes of the third class ( hsp27 and hsp83 —larvae and imagoes) increased after treatment at 41°C temperature. Expression of the first two classes of genes occurred at a temperature lower than the LT50 of larvae and imagoes. The fact that there is a gap between the temperature upregulating hsp genes and the temperature leading to the loss of viability suggests that not only the level of hsp gene expression but also the temperature at which gene expression increased is important in an adaptation of M. scalaris to harsh environment. J. Exp. Zool. 323A: 704–713, 2015 . © 2015 Wiley Periodicals, Inc.